Operation Snow how a Soviet mole in FDR's White House triggered Pearl Harbor - Koster, John (Regnery, 2012)
Recently declassified evidence and never-before-translated documents tell the real story of the day that FDR memorably declared would live in infamy, exploring how Joseph Stalin and the KGB used a vast network of double agents and communist sympathizers--most notably Harry Dexter White--to lead Japan into war against the United States, proposing Soviet involvement behind the bombing of Pearl Harbor